Perjanjian Build Operate And Transfer (Bot) Lapangan Merdeka Medan Dalam Pandangan Hukum Adminsitrasi Negara Dan Hukum Bisnis - Rahmat Ramadhani; Ramlan Ramlan (DE LEGA LATA: JURNAL ILMU HUKUM, 2019)
The BOT agreement is an agreement between the government and investors in terms of mastering and utilizing state assets in the form of land. This writing uses the normative juridical legal research method (normative research) with descriptive analytical research specifications that use secondary data. The procedure for collecting data is in the form of documentation of notes or quotations, search of legal literature, books and others related to the identification of problems both offline and online, which are then analyzed using a legal approach through content analysis method with a focus on the issue of how the application of the BOT principle in the cooperation agreement on development and management of Merdeka Field between Pemko Medan and the private sector? and what is the view of State Administrative Law and Business Law on the BOT agreement in the development and management of Merdeka Field between the Pemko Medan and the private sector ?. From the results of the study it is known that the cooperation agreement between Pemko Medan and the Private Party has implemented the BOT principle by fulfilling the elements of building, managing and submitting the results of development and management by the Investor to Pemko Medan. Furthermore, the said BOT agreement is viewed from the State Administrative Law, an official act of the State administration that has dimensions of public law and private law. Whereas in the view of Business Law the BOT agreement must equally benefit both parties who make the agreement.